Factors Associated With the Health Literacy of Caregivers of Patients Undergoing Cranial Neurological Surgery - Ferraz de Almeida, Graziela Maria [UNESP]; De Albuquerque Gimenez, Viviane Cristina [UNESP]; Rodrigues, Caroline Iaiz [UNESP]; Vitoriano Budri, Aglecia Moda [UNESP]; Hamamoto Filho, Pedro Tadao [UNESP]; Garcia de Avila, Marla Andréia [UNESP] (Elsevier, 2025)
Background: Caregiver health literacy (HL) in patients' transition from hospital to home care is an important factor for good results. Methods: This cross-sectional study included 89 patient-informal caregiver dyads in Brazil. Data were collected using a sociodemographic questionnaire and the European Health Literacy Survey Questionnaire short-short form. Data were analyzed using descriptive statistics, univariate analyses, and a binary logistic regression model. Results: The caregivers’ average age was 48 ± 13.48 years, and 73.0% of them were female. It was found that 6.7% of the caregivers had inadequate HL, 61.8% had problematic HL, and 31.4% had sufficient HL. Being a healthcare professional was significantly associated with sufficient HL (P = 0.016). Furthermore, healthcare workers had more years of schooling than other caregivers (15.3 ± 4.6 vs. 11.2 ± 4.6; P = 0.013). For every 1-year increase in caregiver age, there was a decrease of 0.041 points on the European Health Literacy Survey Questionnaire short-short form. Being a healthcare professional, increased HL scores by 11.4%. Conclusions: Key findings showed that caregivers with higher HL were typically younger, male, better educated, and more likely to be healthcare professionals. These caregivers managed patients with lower dependence on daily activities, while those with lower HL, mainly females, cared for patients with higher dependence. The study highlights the need for targeted interventions and public policies to enhance HL among caregivers, particularly to improve outcomes for patients with complex needs.
Keywords: Caregivers; Cranial neurosurgery; Health literacy; Neurosurgery; Perioperative nursing; Transitional care